Las veleidades saharianas del gobierno Silvela (1900) - Francisco Manuel Pastor Garrigues (Mélanges de la Casa de Velázquez, 2011)
The most salient features of Spanish foreign policy from 1874 were inaction, extreme dependence with respect to the great European powers, and a belief that it must necessarily be an adjunct of the particular and unwavering goals of the Restoration regime. Nevertheless, in the course of the year 1900 the conservative Silvela cabinet embarked on an ambitious policy with regard to the colonial partitioning of the Moroccan Sultanate, far removed from the strategy of defence of the status quo in Morocco pursued by Cánovas. This line of policy consisted in seeking to take hold of the extensive territories in the south of the Sharifian Empire, Tarfaya and Sakia al-Hamra, with the aid of the British government. The central concept in this strategy was based on realpolitik, aimed as it was at protecting national security. However, it ultimately proved ill-fated owing to a lack of pragmatism and political vision on the part of Silvela, who was unable to offer Lord Salisbury’s government anything in return. The British proved highly reluctant to support the conservative government, as the Spanish initiative tended not to uphold the territorial status of the Sharifian Empire but to subvert it.